Anthropological Dimensions of Aḥsan Taqwīm in Surah At-Tīn: A Comparative Study of Hamka’s Tafsīr al-Azhār and Sayyid Qutb’s Fī Ẓilāl al-Qur’ān - Sinaga, Gusti Adrian; Matondang, Husnel Anwar (ZAD Al-Mufassirin, 2025)
This article examined the anthropological meaning of aḥsan taqwīm in Surah At-Tīn through a comparative analysis of Hamka’s Tafsīr al-Azhār and Sayyid Qutb’s Fī Ẓilāl al-Qur’ān. The study was motivated by the differing socio-cultural and ideological backgrounds of the two exegetes, which significantly shape their interpretive orientations. Using a qualitative library-based method and a thematic–comparative approach, this research analyzed how each scholar conceptualizes human dignity, nature, and moral agency within the Qur’anic framework. The findings indicated that Hamka emphasizes the integration of physical, rational, and moral dimensions of human beings, presenting aḥsan taqwīm as a foundation for ethical character and social harmony. In contrast, Qutb foregrounds the spiritual and ideological potential of humanity, framing aḥsan taqwīm as the capacity for transcendence actualized through faith and submission to divine sovereignty. This study concluded that both perspectives highlight human excellence as divinely endowed, yet differ significantly in their anthropological emphasis. The comparison contributes to contemporary Qur’anic anthropology by demonstrating how exegetical interpretations are shaped by contextual realities and by offering a bridge between Southeast Asian and Middle Eastern intellectual traditions.